2006
DOI: 10.7861/clinmedicine.6-2-154
|View full text |Cite
|
Sign up to set email alerts
|

Safety on elective: a survey on safety advice and adverse events during electives

Abstract: -The risk of students contracting HIV on electives has received much coverage. Few data exist, however, on risks of other adverse events. Medical schools gave comprehensive advice on infectious disease but little on personal safety. There were no reported parenteral infections or deaths from infection, despite cases of malaria and one needle-stick injury. Accidents were responsible for six deaths and three serious injuries from just nine medical schools. A further student committed suicide after return to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 9 publications
2
25
0
Order By: Relevance
“…One study estimated the death rate from electives to be as high as 1 in 340-430 (Tyagi et al 2006) with most of the seven reported deaths in this study being due to accidents. Other health risks are also high with minor infectious diseases being most common, although evidence suggests these are no more common than in holidaymakers.…”
Section: Risk-management Of Electivesmentioning
confidence: 71%
See 1 more Smart Citation
“…One study estimated the death rate from electives to be as high as 1 in 340-430 (Tyagi et al 2006) with most of the seven reported deaths in this study being due to accidents. Other health risks are also high with minor infectious diseases being most common, although evidence suggests these are no more common than in holidaymakers.…”
Section: Risk-management Of Electivesmentioning
confidence: 71%
“…Malaria, schistosomiasis, para-typhoid and amoebic dysentery are all reported (Tyagi et al 2006) and pre-departure education must therefore include a number of key areas of basic travel health advice ( Table 2).…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…[12][13][14][15] However, in a 2003 survey, Tyagi et al reported that seven traumatic deaths, five non-fatal road traffic accidents and seven crime-related injuries occurred in the same period as one needlestick injury. 16 POTENTIAL SOLUTIONS It seems that electives can bring benefits to the students who go on them, but that this can perhaps be improved. In addition, there may be scope to improve safety and address some of the ethical imbalances which appear to be inherent within the current system.…”
Section: Moral and Ethical Aspectsmentioning
confidence: 97%
“…One study concluded that "medical students are often poorly prepared for the … safety dilemmas they encounter during these electives" based on a survey of 23 medical students returning from international study 32 . Another study, focusing on accidents among medical students studying abroad, mentioned that there is often a lack of advice on personal safety issues 33 . A Canadian study of medical school faculty also noted gaps in pre-departure planning and concluded that reviews of health and safety should be mandatory for all international electives 34 .…”
Section: Risks and Challengesmentioning
confidence: 99%